Multiinstitutional national study for planning comparison on different anatomical sites. (September 2016) - Marino, Carmelo; Bonanno, Elisa; Borzı̀, Giuseppina R.; Bottalico, Laura; Cagni, Elisabetta; Carbonini, Claudia; Casale, Michelina; Casati, Marta; Clemente, Stefania; Consorti, Rita; D'Alesio, Valentina; Esposito, Marco; et al.
Abstract : Purpose: The SBRT working group of Italian Association of Medical Physics (AIFM) performed 4 multicenter planning studies on patients who were candidates for SBRT in the treatments of prostate, liver, lung and spine cancer with the aim of evaluating the dosimetric consistency among the different hospitals. Methods and materials: Plans were performed following the dose prescription of 35 Gy in five fractions for the planning target volume (PTV) on prostate, 54 Gy in 3 fractions for liver, 75 Gy in 3 fractions for lung and 3 fractions of 10 Gy for spine. Different techniques were used (3D-CRT, fixed-Field IMRT, VMAT, TomoTherapy, CyberKnife) and plans were compared in terms of dose-volume histogram (DVH) parameters. Results: For prostate, important differences were found in terms of the HI. Doses to OARs were heterogeneous. For Liver, no significant correlations between technological factors and DVH for target and OARs were observed; the optimisation strategies selected by the planners played a key role in the planning procedure. For lung, significant correlations for PTV-gEUD2 versus PTV-HI, and MLD2 versus PTV-GI, were observed. Conclusions: Important dosimetric differences with possible clinical implications, in particular related to OARs, were found. Multicenter clinical trials on SBRT should require a preplanning study to standardize the optimization procedure. The differences both in terms of target coverage and OAR sparing suggest inter-comparison of DVH could be a useful tool to standardize treatment planning of stereotactic treatments before starting multicentric clinical trial.